The power of bottom-up and multi-stakeholder approaches to improving the uptake of sustainable household energy technologies in non-OECD economies - Recalde, Marina Yesica (2021)
Energy efficiency and renewable energy technologies in households have a key role for the achievement of the Paris Agreement and to contribute to various SDGs. In pursuit of these objectives, multilateral funds, in conjunction with local governments, design and implement different technology transfer policies. However, the results are very different. In this article we explore recent cases of energy policies to increase the use of renewable and energy efficiency technologies and practices in households in some countries of Latin America, with the aim to identify the key means to closing the gap between technology needs and implementation. We identify two key aspects that determine the impact and result of technology uptake: the elaboration of policies with a bottom-up and multi-stakeholder perspective. With this in mind, we offer some policy recommendations.